A BIBLIOMETRIC ANALYSIS OF INCENTIVES FOR INNOVATION IN PUBLIC POLICY RESEARCH - Pratama, M. Rizki; Hanif Muzaqi, Ajie; Tualeka, Safaruddin Hisyam; Febi Wulandari, Ni Putu; Maharani, Anisa (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2025)
This study examines 392 Scopus-indexed publications (1975–2025) on innovation incentives in public policy using bibliometric methods through the Bibliometrix® application. Findings show a 7.66% annual growth rate, accelerating after 2010 as innovation incentives gained prominence in sustainability and digital transformation agendas. Research output is concentrated in core journals such as Sustainability (Switzerland), Research Policy, and the Journal of Cleaner Production, with Research Policy leading in scholarly impact. Keyword analysis and thematic mapping indicate a shift from fiscal and regulatory instruments toward broader themes of sustainability, governance, and organizational culture. Thematic evolution further reflects a movement from sector-specific cases, such as pharmaceuticals, to systemic perspectives on collaborative innovation and green development. Conceptual and co-occurrence analyses reveal two dominant orientations: one focused on economic and regulatory tools, the other on governance and sustainability. International collaboration networks highlight North America, Europe, and China as key hubs, while Latin America and Africa remain more regionally confined, underscoring global research asymmetries. Overall, the field is rapidly expanding and interdisciplinary but remains fragmented, with limited theoretical integration and uneven geographic representation. Strengthening comparative frameworks and fostering North–South collaboration are essential for more inclusive and context-sensitive policy insights.